2018
DOI: 10.1055/s-0038-1667037
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Polymorphism in MTHFR SNPs (677 and 1298) in Paternal Sperm DNA is Associated with an Increased Risk of Retinoblastoma in Their Children: A Case–Control Study

Abstract: Sperm DNA is considered as the most vulnerable to oxidative stress-induced damage that also impairs global sperm DNA methylation leading to sperm-associated pathologies. C677T and A1298C polymorphisms of the methylene tetrahydrofolate reductase gene affect MTHFR enzyme activity. This study was planned as a case-control study to determine the gene polymorphisms in the fathers of children affected with sporadic nonfamilial heritable retinoblastoma in an Indian population. polymorphisms for single nucleotide poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Therefore, they have found a strong association of the MTHFR 677C>T and 1298A>C polymorphisms with retinoblastoma pathogenesis in an Indian population. They have suggested a possible and important role of a one-carbon metabolism pathway, methylation regulation, and an increased risk of retinoblastoma initiation [25]. Inconsistent with our results, the previous study in the Iranian population demonstrated that MTHFR 677C>T is associated with retinoblastoma.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, they have found a strong association of the MTHFR 677C>T and 1298A>C polymorphisms with retinoblastoma pathogenesis in an Indian population. They have suggested a possible and important role of a one-carbon metabolism pathway, methylation regulation, and an increased risk of retinoblastoma initiation [25]. Inconsistent with our results, the previous study in the Iranian population demonstrated that MTHFR 677C>T is associated with retinoblastoma.…”
Section: Resultssupporting
confidence: 87%
“…It is a mandatory process in transmission of life: it is a major regulator in gametogenesis, embryo development, and growth via, but only, its role in epigenesis and imprinting mechanisms [8]. Since excess Hcy and the presence of MTHFR SNPs increase pathology risks in general [9][10][11][12], the risk of infertility at all stages pre-and postconception [13][14][15][16][17][18], the frequency of miscarriage [6,19,20], and compromised infant health [21][22][23], we have determined retrospectively the prevalence of the two main MTHFR SNPs in our population of 2970 male and female patients consulting for infertility; serum homocysteine levels were assessed in parallel.…”
Section: Introductionmentioning
confidence: 99%